Hepatoid adenocarcinoma of the stomach: Histopathologic and immunohistochemicalanalysis of three cases - Makbule ARAR; Tahir Ercan PATIROĞLU; Olgun Kontaş; Yücel TEKİN (Turkish Journal of Gastroenterology, 2019)
-